2003
DOI: 10.1046/j.1364-3703.2003.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Quinoxyfen perturbs signal transduction in barley powdery mildew (Blumeria graminis f.sp. hordei)

Abstract: SUMMARY Quinoxyfen is a protectant fungicide which controls powdery mildew diseases by interfering with germination and/or appressorium formation. Mutants of barley powdery mildew, Blumeria graminis f.sp. hordei, which are resistant to quinoxyfen produce fewer conidia, which germinate and form appressoria more promiscuously than do the prolific numbers of wild‐type spores. This suggests that resistance bypasses host recognition signals. RT‐PCR profiles of signal transduction genes, recorded during wild‐type ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Nowadays, several fungicides are used to control diseases in grapes: famoxadone, oxazolidinone known for its effective, wideranging prevention of various foliar fungal diseases (Bartlett et al, 2002;Jernberg, 2003); fenhexamid, hydroxyanilide used in the control of Botrytis cinerea in grapes (Duben, Rosslenbroich, & Jenner, 2002); fluquinconazole, thiazole used in the control of Uncinula necator (Metcalfe, Shaw, & Russell, 2000); kresoximmethyl, oxymino acetate (strobilurin) used to control U. necator in grapes (Grossmann & Retzlaff, 1999); quinoxyfen, a quinoline used in grapes to control powdery mildew (U. necator) (Wheeler et al, 2003); and trifloxystrobin, an active strobilurin to combat powdery mildew in grapes (De Melo, Correia, Herbet, Santos, & Alves, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several fungicides are used to control diseases in grapes: famoxadone, oxazolidinone known for its effective, wideranging prevention of various foliar fungal diseases (Bartlett et al, 2002;Jernberg, 2003); fenhexamid, hydroxyanilide used in the control of Botrytis cinerea in grapes (Duben, Rosslenbroich, & Jenner, 2002); fluquinconazole, thiazole used in the control of Uncinula necator (Metcalfe, Shaw, & Russell, 2000); kresoximmethyl, oxymino acetate (strobilurin) used to control U. necator in grapes (Grossmann & Retzlaff, 1999); quinoxyfen, a quinoline used in grapes to control powdery mildew (U. necator) (Wheeler et al, 2003); and trifloxystrobin, an active strobilurin to combat powdery mildew in grapes (De Melo, Correia, Herbet, Santos, & Alves, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, over the last decade, several studies have strongly suggested that some fungicides may also interfere with fungal intracellular signal transduction pathways. Quinoxyfen, a phenoxyquinoline introduced for control of powdery mildew diseases, has been shown to inhibit mildew infection by disrupting G‐protein production and early cell signalling events (Wheeler et al ., 2003). Dicarboximide fungicides (DCF), which are highly active broad‐spectrum compounds, and phenylpyrolles, which have mainly been used to control Botrytis cinerea , are both believed to exert their toxic effects on fungi through activation of the osmoregulation pathway (Kojima et al ., 2004; Ma & Michailides, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact site of action of quinoxyfen has not yet been determined, its effects have been linked to disruption of early cell signalling events in Blumeria graminis Speer f. sp. hordei Marchal (Bgh) 5. Because it acts on early stages of development, it has been demonstrated that quinoxyfen is only successful in preventing infection and eventual colony development if it is present within the first 4–6 h after Bgh contacts a host plant (Dow AgroSciences, unpublished).…”
Section: Introductionmentioning
confidence: 99%